MEASURING THE RELEGIOSITY OF A MOSLEM ACCORDING TO INN HAJAR AL-ASQALANI - Mifdlol - Muthohar (Pondok Pesantren Modern Islam Assalaam, 2017)
This research based on the needs of explanation about five dimensions of religiousity written by Glock and Stark which then modified by Nashori and Mucharam with the adjustment toward religiousity in Islam. This is a Qualitative research with analytic descriptive approach. The result shows that there are 69 religious points of a moslem sourced from Al-Hadits about branches of faith. Those 69 points could be explained into 5 dimensions. Those dimensions consisted of Dimension of Aqidah 10 points, Dimension of Syariah 16 points, Dimension of Akhlaq 29 points, Dimension of Knowledge 3 points and Dimension of Ihsan 11 points.